2021
DOI: 10.17306/j.jard.2021.01439
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of non-farm enterprises on poverty status of rural farming households in Nigeria

Abstract: This study evaluates the impact of non-farm enterprises on the poverty status of rural farming households in Nigeria. The data were obtained from General Household Survey fielded by the National Bureau of Statistics in 2010/2011 and 2015/2016. However, only 1,619 matched observations were used for analyses, using Propensity Score Matching, Double Difference, Foster-Greer-Thorbecke poverty measures and Poverty Equivalent Growth Rates (PEGRs). The results show that 53.3% of participants lived below the poverty l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Figure 4 unveil the household size of the respondents revealed that majority (55.5%) had 6-15 household size, and having 6-20 occupying (75.2%) implies that greater majority had adequate household size to curtail labor costs to be incurred. Conversely, [25] found that both the farmers that have access River Basin Development Authority facilities and those without access, have approximately 4 household members. The findings of education in Figure 5 adduce that (62.4%) had Islamic education and (23.1%) had primary and secondary education respectively, an indication that, more than two-third (85.5%) had limited western education to be conversant with irrigation practices that posed serious threat to food security.…”
Section: Discussion Of Findingsmentioning
confidence: 95%
“…Figure 4 unveil the household size of the respondents revealed that majority (55.5%) had 6-15 household size, and having 6-20 occupying (75.2%) implies that greater majority had adequate household size to curtail labor costs to be incurred. Conversely, [25] found that both the farmers that have access River Basin Development Authority facilities and those without access, have approximately 4 household members. The findings of education in Figure 5 adduce that (62.4%) had Islamic education and (23.1%) had primary and secondary education respectively, an indication that, more than two-third (85.5%) had limited western education to be conversant with irrigation practices that posed serious threat to food security.…”
Section: Discussion Of Findingsmentioning
confidence: 95%
“…Poverty stands as a pervasive global challenge, compelling governments worldwide to prioritize its alleviation. In 2015, over 736 million people lived below the poverty line, with pre-pandemic projections indicating persistent struggles for basic necessities among 10% of the global population (Kolawole, 2021;Matta, 2020). The COVID-19 outbreak, compounded by economic upheavals such as inflation and geopolitical tensions, has exacerbated poverty levels, potentially pushing an additional 75 million to 95 million individuals into extreme poverty by 2022 (Moyer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%